Left pilaster of the Antarala of the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
The pilaster on the left side of the antarala (vestibule or antechamber) of the Kaner-ki-Putli Temple depicts a standing ascetic with folded hands. He has thick, matted hair locks, a long beard, and a mustache. His upper body is bare, while his lower body is clad in a langot (loincloth).